THE MAIN DIRECTIONS OF ECONOMIC DEVELOPMENT AND ASSESSMENT OF INTEGRATION EFFECTS IN THE EURASIAN ECONOMIC UNION IN THE CONDITIONS OF GLOBAL CHALLENGES - R., Aroupova N.; M., Abaidullayeva M.; A., Arupova N. (Farabi Journal of Social Sciences, 2019)
Abstract.This article considers the strategic directions of economic development of the member states of the Eurasian Economic Union, based on available resources and objective opportunities for their joint effective use. With all the turbulence and uncertainty that exist today in the world economy, the definition of the main directions for the coordination of economic policies looks extremely important and timely. In general, by 2030, the results of the economic development of the EAEU have to show the world competitiveness of the integration association. In the 2030s, the economic development of the EAEU would be possible to overcome the competitive advantages of integration integration. The Customs Union of Kazakhstan, Belarus and Russia is a logical breakthrough from the Eurasian Economic Community. Established in 2000 in the format of Belarus, Kazakhstan, Kyrgyzstan, Russia and Tadjikistan – a momentous moment in the practice of the Eurasian integration. For all 11 years EurAsEC has been shaped by the mechanism of differentiation of mechanisms in the integration process. By the way, they do not just become intergovernmental, but also by initiative entrepreneurs, educators, education and culture, NGOs, and youth. With the help of the global financial and economic crisis, the creation of the Eurasian bank was undermined by the anti crisis. Kazakhstan considers Eurasia Union as an open project. Его нельзя предстaвить без междунaродному общественности, нaпример, с Евросоюзом, with other convergence. Astana observes that the Euroasian Soyuz propiska is a defensive part of the Chinese definition of economic expansion. Key words: ЕАEU, integration effects, Eurasian integration.